An unsaturated silane-polyazomine glycidyl ether co-coated aluminum lithium alloy powder and a method for preparing the same
Patent Information
- Application Number
- CN202411023326.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-07-29
AI Technical Summary
Traditional aluminum powder has a high ignition temperature and long ignition delay time in propellants, resulting in slow combustion and easy agglomeration. The high reactivity of aluminum-lithium alloy powder leads to structural defects such as pores and cracks caused by its reaction with propellant components.
The stability and energy level of aluminum-lithium alloy powder are improved by using a method of co-coating with unsaturated silane-polyazidoglycidyl ether, forming a dense coating layer on the surface of the powder and attaching a noble metal catalyst.
This method improves the stability and combustion performance of aluminum-lithium alloy powder. Furthermore, it introduces high-energy groups onto the surface of the alloy powder, resulting in a higher calorific value compared to the original powder and aluminum-lithium alloy powder without a specific catalyst. This enhances the combustion performance, calorific value, and stability of the aluminum-lithium alloy powder.
Smart Images

Figure CN118955230B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether and its preparation method, belonging to the field of energetic materials technology. Background Technology
[0002] Metallic fuels are an important component of modern solid propellants, enhancing their heat of combustion and detonation velocity. Simultaneously, the metal oxide particles generated during combustion suppress oscillatory combustion. Aluminum powder, due to its high density, low oxygen consumption, and high enthalpy of combustion, is widely used in solid propellants, significantly improving specific impulse.
[0003] However, the application of aluminum powder in propellants also has some drawbacks. Traditional micron-sized aluminum powder, due to its high ignition temperature, long ignition delay, and tendency to agglomerate into large aluminum droplets during combustion, exhibits slow and incomplete combustion, significantly reducing its combustion efficiency. Therefore, to improve the combustion performance of solid propellants, metallic fuels need to be selected and adjusted according to specific needs and conditions to fully utilize their advantages and minimize their disadvantages.
[0004] Compared to other aluminum-based alloy fuels, aluminum-lithium alloy powder has significant advantages in propellant applications. Firstly, as an ideal alloy fuel, aluminum-lithium alloy powder possesses high heat release and produces micro-explosions during combustion, significantly improving propellant combustion efficiency. Compared to traditional aluminum powder, aluminum-lithium alloy powder has a higher ignition success rate and a relatively lower ignition temperature. However, the high reactivity of aluminum-lithium alloy powder also leads to structural defects such as porosity and cracks caused by its reaction with propellant components. To address this issue, surface coating technology can be used to improve the stability and compatibility of aluminum-lithium alloy powder. Furthermore, coating it with high-energy materials can further enhance its energy level. Summary of the Invention
[0005] In view of this, the purpose of the present invention is to provide an aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether and a method for preparing the same.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows.
[0007] An aluminum-lithium alloy powder co-coated with unsaturated silane and poly(azide glycidyl ether) is disclosed. The surface of the aluminum-lithium alloy powder is coated with an unsaturated silane coupling agent, and poly(azide glycidyl ether) is grafted onto the unsaturated silane coupling agent to form a second coating layer. Simultaneously, a noble metal catalyst is also attached to the aluminum-lithium alloy powder; the atomic radius of the noble metal catalyst is [missing information].
[0008] Preferably, the coating thickness of the unsaturated silane coupling agent is 30-40 nm, the coating thickness of the polyazidoglycidyl ether is 15-20 nm, and the amount of the noble metal catalyst attached is less than 3% of the mass of the aluminum-lithium alloy powder.
[0009] Preferably, the unsaturated silane coupling agent is one or more of 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltri(2-methoxyethoxy)silane.
[0010] Preferably, the molecular weight of the polyazoglycolic acid ether is 3500 to 4500.
[0011] Preferably, the noble metal catalyst is one or more of platinum, palladium, ruthenium, and silver.
[0012] Preferably, the aluminum-lithium alloy powder contains 93% to 95% aluminum by mass and 5% to 7% lithium by mass.
[0013] Preferably, the particle size of the aluminum-lithium alloy powder is 5μm to 50μm.
[0014] A method for preparing aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether according to the present invention, comprising the following steps:
[0015] (1) Hydrolyze the unsaturated silane coupling agent in an alcohol solution for 20-30 min to obtain a hydrolyzed silane coupling agent solution;
[0016] (2) Add aluminum-lithium alloy powder to an organic solvent and disperse it evenly. Then add the hydrolyzed silane coupling agent solution and stir for 30-50 minutes to form a dense coating layer on the surface of the aluminum-lithium alloy powder. After centrifugation, washing and drying, aluminum-lithium alloy powder coated with unsaturated silane coupling agent is obtained.
[0017] (3) The aluminum-lithium alloy powder coated with unsaturated silane coupling agent is added to an organic solvent and dispersed evenly. A noble metal catalyst is added, and the mixture is heated to 65-85°C. An organic solution of polyazidoglycidyl ether is added dropwise, and the mixture is kept warm and stirred for 40-60 minutes. After centrifugation, washing, and drying, an aluminum-lithium alloy powder co-coated with unsaturated silane and polyazidoglycidyl ether is obtained.
[0018] Preferably, the amount of unsaturated silane coupling agent added is 10% to 30% of the mass of aluminum-lithium alloy powder, the amount of noble metal catalyst added is 0.5% to 3% of the mass of aluminum-lithium alloy powder, and the amount of polyazidoglycidyl ether added is 8% to 15% of the mass of aluminum-lithium alloy powder.
[0019] Preferably, the organic solvent is one or more of tetrahydrofuran, ethyl acetate, and acetone.
[0020] Preferably, in step (1), the pH of the alcohol solution is 4-5. More preferably, the alcohol is ethanol and / or methanol. Hydrolysis in an alcohol solution with a pH of 4-5 effectively promotes the hydrolysis reaction and provides a reaction environment for subsequent steps.
[0021] Application of an unsaturated silane-polyazidoglycidyl ether co-coated aluminum-lithium alloy powder as a metallic fuel in solid propellants.
[0022] Beneficial effects
[0023] This invention employs unsaturated silane-poly(azidoglycidyl ether) co-coating. The co-coating is achieved through chemical grafting, resulting in a more robust coating layer with noble metal adhering to the surface. This improves both the stability and energy of the aluminum-lithium alloy powder. The calorific value of the co-coated aluminum-lithium alloy powder is significantly higher than that of the original powder or aluminum-lithium alloy powder coated with a single silane coupling agent. The addition of poly(azidoglycidyl ether) introduces high-energy groups onto the alloy powder surface, leading to a significant increase in calorific value. Simultaneously, the noble metal adhering to the surface further enhances the combustion performance of the aluminum-lithium alloy powder, which is beneficial for its application in propellants. Attached Figure Description
[0024] Figure 1 The images show a comparison of scanning electron microscope (SEM) images of aluminum-lithium alloy powder (a) co-coated with unsaturated silane-polyazide glycidyl ether in Example 1, aluminum-lithium alloy powder (b), aluminum-lithium alloy powder (c) in Comparative Example 1, and aluminum-lithium alloy powder (d) in Comparative Example 2.
[0025] Figure 2 This is a comparison of the stability of the aluminum-lithium alloy powder co-coated with unsaturated silane-polyazide glycidyl ether in Example 1 (right) and the initial aluminum-lithium alloy powder (left) in the liquid phase.
[0026] Figure 3 Infrared spectral analysis of the aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether in Example 1, the original aluminum-lithium alloy powder, and the aluminum-lithium alloy powder with single coating of unsaturated silane.
[0027] Figure 4 This is a depth profile of silicon and nitrogen elements in the aluminum-lithium alloy powder of Example 1. Detailed Implementation
[0028] The present invention will be further described in detail below with reference to specific embodiments.
[0029] In the following examples or comparative examples, the molecular weight of polyazidoglycidyl ether is 3656.
[0030] Example 1
[0031] Add an appropriate amount of methanol to a small beaker, adjust the pH to 4, add 0.5g of 3-methacryloxypropyltrimethoxysilane to the solution, and stir for 20 minutes. Add 70ml of ethyl acetate to a three-necked flask, then add 5g of aluminum-lithium alloy powder (lithium content 6%, particle size 30μm), mix well, and then add 3-methacryloxypropyltrimethoxysilane hydrolysis solution dropwise, stirring for 40 minutes to fully coat the aluminum-lithium alloy surface with unsaturated silane. After centrifugation, washing, and drying under vacuum, add the mixture to a three-necked flask containing 70ml of ethyl acetate, add 0.05g of platinum catalyst, heat to 70℃, and add 5g of poly(azide glycidyl ether) ethyl acetate solution (poly(azide glycidyl ether) mass fraction 10%) dropwise, stirring for 50 minutes. After centrifugation, washing, and drying under vacuum, an aluminum-lithium alloy powder co-coated with unsaturated silane and poly(azide glycidyl ether) is obtained.
[0032] Comparative Example 1
[0033] Add an appropriate amount of methanol to a small beaker, adjust the pH to 4, add 0.2g of propyltrimethoxysilane to the solution, and stir for 20 minutes. Add 30ml of ethyl acetate to a three-necked flask, then add 2g of aluminum-lithium alloy powder (lithium content 6%, particle size 30μm), mix well, and then add propyltrimethoxysilane hydrolysis solution dropwise, stirring for 30 minutes to fully coat the aluminum-lithium alloy surface with silane. After centrifugation, washing, and drying under vacuum, add the mixture to a three-necked flask containing 30ml of ethyl acetate, add 0.02g of platinum catalyst, heat to 70℃, and add 2g of poly(azide glycidyl ether) ethyl acetate solution (poly(azide glycidyl ether) mass fraction 10%) dropwise, stirring for 30 minutes. After centrifugation, washing, and drying under vacuum, a coated aluminum-lithium alloy powder is obtained.
[0034] Comparative Example 2
[0035] Add an appropriate amount of methanol to a small beaker, adjust the pH to 4, and add 0.2g of 3-methacryloxypropyltrimethoxysilane to the solution. Stir for 20 minutes. Add 30ml of ethyl acetate to a three-necked flask, then add 2g of aluminum-lithium alloy powder (lithium content 6%, particle size 30μm). Mix well, then add 3-methacryloxypropyltrimethoxysilane hydrolysis solution dropwise. Stir for 30 minutes to fully coat the aluminum-lithium alloy surface with unsaturated silane. Centrifuge, wash, and dry under vacuum conditions, then add to a three-necked flask containing 30ml of ethyl acetate. Heat to 70℃, and add 2g of poly(azide glycidyl ether) ethyl acetate solution (poly(azide glycidyl ether) mass fraction 10%) dropwise. Stir for 30 minutes, centrifuge, wash, and dry under vacuum conditions to obtain a coated aluminum-lithium alloy powder.
[0036] Comparative Example 3
[0037] Add an appropriate amount of methanol to a small beaker, adjust the pH to 4, add 0.2g of 3-methacryloxypropyltrimethoxysilane to the solution, and stir for 20 minutes. Add 30ml of ethyl acetate to a three-necked flask, then add 2g of aluminum-lithium alloy powder (lithium content 6%, particle size 30μm), mix well, and then add 3-methacryloxypropyltrimethoxysilane hydrolysis solution dropwise, stirring for 30 minutes to fully coat the unsaturated silane on the surface of the aluminum-lithium alloy. After centrifugation, washing, and drying under vacuum, add the mixture to a three-necked flask containing 30ml of ethyl acetate, add 0.02g of boron trifluoride triethanolamine, heat to 70℃, and then add 2g of poly(azide glycidyl ether) ethyl acetate solution (poly(azide glycidyl ether) mass fraction 10%) dropwise, stirring for 30 minutes. After centrifugation, washing, and drying under vacuum, a coated aluminum-lithium alloy powder is obtained.
[0038] Electron micrograph of the aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether described in Example 1 after 7 days of storage ( Figure 1 (a) Electron micrograph of aluminum-lithium alloy powder after 7 days of storage. Figure 1 (b) Electron micrographs of aluminum-lithium alloy powder in Comparative Example 1 after 7 days of storage. Figure 1 (c) Electron micrographs of aluminum-lithium alloy powder in Comparative Example 2 after 7 days of storage. Figure 1 Compare with d), such as Figure 1 As shown, the comparison revealed that the aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether described in Example 1 still had a dense coating layer. In contrast, the original aluminum-lithium alloy powder was completely oxidized, and the coating layers of the aluminum-lithium alloy powder in Comparative Examples 1 and 2 showed significant flaking over varying degrees. This indicates that the aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether prepared in Example 1 exhibits better storage performance compared to aluminum-lithium alloy powder coated with unsaturated silane coupling agent and aluminum-lithium alloy powder without catalyst-coated polyazidoglycidyl ether.
[0039] The aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether described in Example 1 and the initial aluminum-lithium alloy powder were compared by placing them in hot water at 70°C. Figure 2 As shown in the image (right) of the co-coated aluminum-lithium alloy powder in this embodiment after being placed in hot water at 70°C for 3 hours, it can be seen that the alloy powder did not react with the water. The image (left) of the initial aluminum-lithium alloy powder in water shows a violent reaction. This indicates that the unsaturated silane-polyazidoglycidyl ether co-coated aluminum-lithium alloy powder in Example 1 has a certain degree of stability in the liquid phase environment.
[0040] The heat of combustion of aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether as described in Example 1, the original aluminum-lithium alloy powder, and the coated aluminum-lithium alloy powder in Comparative Example 3 were measured using an oxygen-nitrogen calorimeter, as shown in Table 1. The heat of combustion of the co-coated lithium alloy powder described in Example 1 was significantly higher than that of the original powder and the aluminum-lithium alloy powder without a specific catalyst. This indicates that the addition of polyazidoglycidyl ether introduces high-energy groups on the surface of the alloy powder, and these high-energy groups lead to a significant increase in heat value. Spot scanning of the aluminum-lithium alloy powders in Example 1 and Comparative Example 3 was performed using an energy dispersive spectroscopy (EDS) instrument, as shown in Table 2. The presence of platinum indicates that the specific metal catalyst used in Example 1 adheres to the aluminum-lithium alloy powder during the reaction, and this adhesion of the metal catalyst can increase the heat of combustion. This demonstrates that the unsaturated silane-polyazidoglycidyl ether co-coating method described in this invention improves both the stability and energy of the aluminum-lithium alloy powder.
[0041] Table 1
[0042]
[0043] Table 2
[0044]
[0045] To verify that the unsaturated silane and polyazidoglycidyl ether described in Example 1 were both coated on the aluminum-lithium alloy powder, FTIR tests were performed on both powder and the original powder. The results are as follows: Figure 3 As shown, carbon-carbon double bonds (1630 cm⁻¹) exist on the aluminum-lithium alloy powder coated with silane coupling agent. -1 ) and carbon-oxygen double bond (1582cm) -1 The characteristic peaks at 2316 cm⁻¹ prove that silane coupling is grafted onto the surface of the alloy powder. The characteristic peaks of carbon-carbon double bonds disappear on the co-coated aluminum-lithium alloy, and azide groups appear (2316 cm⁻¹). -1 Characteristic peaks and carbon and nitrogen peaks (1142 cm⁻¹) -1 This demonstrates that poly(azide glycidyl ether) was successfully coated onto the alloy powder coated with the silane coupling agent. The depth profile curve shows that... Figure 4 As shown, in Example 1, the mass of unsaturated silane used in the co-coating of aluminum-lithium alloy powder with unsaturated silane and polyazidoglycidyl ether is 10% of the mass of the aluminum-lithium alloy powder, and the coating layer thickness is about 35 nm. The mass of polyazidoglycidyl ether is 10% of the mass of the aluminum-lithium alloy powder, and the coating layer thickness is about 15 nm.
[0046] Example 2
[0047] Add an appropriate amount of ethanol to a small beaker, adjust the pH to 4.5, add 0.5g of 3-methacryloxypropyltriethoxysilane to the solution, and stir for 25 minutes. Add 70ml of ethyl acetate to a three-necked flask, then add 5g of aluminum-lithium alloy powder (lithium content 6%, particle size 30μm), mix well, and then add 3-methacryloxypropyltriethoxysilane hydrolysis solution dropwise, stirring for 40 minutes to fully coat the aluminum-lithium alloy surface with unsaturated silane. After centrifugation, washing, and drying under vacuum, add the mixture to a three-necked flask containing 70ml of ethyl acetate, add 0.05g of platinum catalyst, heat to 75℃, and add 7.5g of poly(azide glycidyl ether) ethyl acetate solution (poly(azide glycidyl ether) mass fraction 10%) dropwise, stirring for 45 minutes. After centrifugation, washing, and drying under vacuum, an aluminum-lithium alloy powder co-coated with unsaturated silane and poly(azide glycidyl ether) is obtained.
[0048] The aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether described in this embodiment still has a dense coating layer after being placed for 7 days.
[0049] When the aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether described in this embodiment was placed in hot water at 70°C for 3 hours, no reaction occurred between the alloy powder and the water. This indicates that the aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether described in this embodiment also exhibits stability in a liquid phase environment.
[0050] In this embodiment, the unsaturated silane and poly(azidoglycidyl ether) were both coated onto the aluminum-lithium alloy powder. The infrared spectrum of the powder showed characteristic peaks of azide groups and carbon-nitrogen peaks, proving that the poly(azidoglycidyl ether) was successfully coated onto the alloy powder coated with the silane coupling agent. The spectrum results also indicated the presence of platinum.
[0051] The co-coated lithium alloy powder described in this embodiment has a significantly higher calorific value than the original aluminum-lithium alloy powder. The addition of poly(azide glycidyl ether) introduces high-energy groups onto the surface of the alloy powder, which leads to a significant increase in calorific value. The adhesion of the metal catalyst further enhances the heat of combustion.
[0052] Example 3
[0053] Add an appropriate amount of methanol to a small beaker, adjust the pH to 5, add 0.2g of vinyltrimethoxysilane to the solution, and stir for 30 minutes. Add 30ml of acetone to a three-necked flask, then add 2g of aluminum-lithium alloy powder (lithium content 6%, particle size 30μm), mix well, and then add vinyltrimethoxysilane hydrolysis solution dropwise, stirring for 30 minutes to fully coat the aluminum-lithium alloy surface with unsaturated silane. After centrifugation, washing, centrifugation again, and drying, add the mixture to a three-necked flask containing 30ml of tetrahydrofuran, add 0.02g of ruthenium catalyst, heat to 65℃, and add 1.6g of polyazidoglycidyl ether tetrahydrofuran solution (polyazidoglycidyl ether mass fraction 10%) dropwise. Stir for 40 minutes, centrifuge, wash, centrifuge again, and dry to obtain an aluminum-lithium alloy powder co-coated with unsaturated silane and polyazidoglycidyl ether.
[0054] The aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether described in this embodiment still has a dense coating layer after being placed for 7 days.
[0055] When the aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether described in this embodiment was placed in hot water at 70°C for 3 hours, no reaction occurred between the alloy powder and the water. This indicates that the aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether described in this embodiment also exhibits stability in a liquid phase environment.
[0056] In this embodiment, the unsaturated silane and polyazidoglycidyl ether were both coated onto the aluminum-lithium alloy powder. The infrared spectrum of the powder showed characteristic peaks of azide groups and carbon and nitrogen peaks, proving that the polyazidoglycidyl ether was successfully coated onto the alloy powder coated with the silane coupling agent. The spectrum results also indicated the presence of ruthenium.
[0057] The co-coated lithium alloy powder described in this embodiment has a significantly higher calorific value than the original aluminum-lithium alloy powder. The addition of poly(azide glycidyl ether) introduces high-energy groups onto the surface of the alloy powder, which leads to a significant increase in calorific value. The adhesion of the metal catalyst further enhances the heat of combustion.
[0058] Example 4
[0059] Add an appropriate amount of ethanol to a small beaker, adjust the pH to 4.5, add 1g of vinyltriethoxysilane to the solution, and stir for 30 minutes. Add 100ml of acetone to a three-necked flask, then add 10g of aluminum-lithium alloy powder (lithium content 6%, particle size 30μm), mix well, and then add vinyltriethoxysilane hydrolysis solution dropwise, stirring for 45 minutes to fully coat the aluminum-lithium alloy surface with unsaturated silane. After centrifugation, washing, centrifugation again, and drying, add the mixture to a three-necked flask containing 100ml of tetrahydrofuran, add 0.01g of silver catalyst, heat to 65℃, and add 15g of poly(azide glycidyl ether) tetrahydrofuran solution (poly(azide glycidyl ether) mass fraction 10%) dropwise, stirring for 40 minutes, centrifugation, washing, centrifugation again, and drying to obtain an aluminum-lithium alloy powder co-coated with unsaturated silane and poly(azide glycidyl ether).
[0060] The aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether described in this embodiment still has a dense coating layer after being placed for 7 days.
[0061] The aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether described in this embodiment was placed in hot water at 70°C for 3 hours, and no reaction occurred between the alloy powder and water. This indicates that the aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether in this example also exhibits stability in a liquid phase environment.
[0062] In this embodiment, the unsaturated silane and polyazidoglycidyl ether were both coated on the aluminum-lithium alloy powder. The infrared spectrum of the powder showed characteristic peaks of azide groups and carbon-nitrogen peaks, proving that the polyazidoglycidyl ether was successfully coated on the alloy powder coated with the silane coupling agent. The spectrum results also indicated the presence of silver.
[0063] The co-coated lithium alloy powder described in this embodiment has a significantly higher calorific value than the original aluminum-lithium alloy powder. The addition of poly(azide glycidyl ether) introduces high-energy groups onto the surface of the alloy powder, which leads to a significant increase in calorific value. The adhesion of the metal catalyst further enhances the heat of combustion.
[0064] In summary, the invention includes, but is not limited to, the above embodiments. Any equivalent substitutions or partial improvements made under the spirit and principles of this invention shall be considered to be within the protection scope of this invention.
Claims
1. An aluminum-lithium alloy powder co-coated with unsaturated silane-poly(azidoglycidyl ether), characterized in that: The surface of the aluminum-lithium alloy powder is coated with an unsaturated silane coupling agent, and poly(azide glycidyl ether) is grafted onto the unsaturated silane coupling agent to form a second coating layer. At the same time, a noble metal catalyst is also attached to the aluminum-lithium alloy powder; the atomic radius of the noble metal catalyst is 1.30~1.90 Å.
2. The aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether as described in claim 1, characterized in that: The coating thickness of the unsaturated silane coupling agent is 30-40 nm, the coating thickness of the polyazidoglycidyl ether is 15-20 nm, and the amount of the noble metal catalyst attached is less than 3% of the mass of the aluminum-lithium alloy powder.
3. The aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether as described in claim 1, characterized in that: The unsaturated silane coupling agent is one or more of 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltri(2-methoxyethoxy)silane.
4. The aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether as described in claim 1, characterized in that: The molecular weight of the polyazidoglycidyl ether is 3500~4500.
5. The aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether as described in claim 1, characterized in that: The precious metal catalyst is one or more of platinum, palladium, ruthenium, and silver.
6. The aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether as described in claim 1, characterized in that: The aluminum-lithium alloy powder contains 93% to 95% aluminum by mass and 5% to 7% lithium by mass; the particle size of the aluminum-lithium alloy powder is 5 μm to 50 μm.
7. A method for preparing aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether as described in any one of claims 1 to 6, characterized in that: The method steps include: (1) Hydrolyze the unsaturated silane coupling agent in an alcohol solution for 20-30 min to obtain a hydrolyzed silane coupling agent solution; (2) Add aluminum-lithium alloy powder to an organic solvent and disperse it evenly. Then add the hydrolyzed silane coupling agent solution and stir for 30-50 minutes to form a dense coating layer on the surface of the aluminum-lithium alloy powder. After centrifugation, washing and drying, aluminum-lithium alloy powder coated with unsaturated silane coupling agent is obtained. (3) The aluminum-lithium alloy powder coated with unsaturated silane coupling agent is added to an organic solvent and dispersed evenly. A noble metal catalyst is added, and the mixture is heated to 65~85℃. An organic solution of polyazidoglycidyl ether is added dropwise, and the mixture is kept warm and stirred for 40~60 min. After centrifugation, washing, and drying, an aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether is obtained.
8. The method for preparing an aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether as described in claim 7, characterized in that: The amount of unsaturated silane coupling agent added is 10% to 30% of the mass of aluminum-lithium alloy powder, the amount of noble metal catalyst added is 0.5% to 3% of the mass of aluminum-lithium alloy powder, and the amount of polyazidoglycidyl ether added is 8% to 15% of the mass of aluminum-lithium alloy powder.
9. The method for preparing an aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether as described in claim 7, characterized in that: The organic solvent is one or more of tetrahydrofuran, ethyl acetate, and acetone; the pH of the alcohol solution is 4-5.
10. The method for preparing an aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether as described in claim 9, characterized in that: The alcohols are ethanol and / or methanol.
11. The application of an aluminum-lithium alloy powder co-coated with unsaturated silane-polyazidoglycidyl ether as described in any one of claims 1 to 6 as a metallic fuel in a solid propellant.
Citation Information
Patent Citations
Sodium carboxymethyl cellulose-glycidyl azide polymer co-coated aluminum lithium alloy powder and preparation method thereof
CN118496047A
